Diversity at the Head Table : Bringing Complementary Skills and Experiences to the Board - Argüden, Yılmaz (World Bank, Washington, DC, 2012)
A well-functioning board of directors needs diversity of experience and perspectives. If everybody thinks the same, then there is no need for a board; one individual would suffice! Diversity for its own sake, however, is not an improvement in governance; what matters is the combination of complementary skills and experiences that members bring to the table to better address the challenges the company is likely to face. This paper provides examples that help develop a better understanding of each type of diversity needed on boards. Author sees diversity as much more than gender or race-including such other factors as experience, nationality, age, and tenure on the board. He also sees the mix of people on boards changing, depending on the business scales and stages of business life cycles.